2012
DOI: 10.1186/1756-0500-5-38
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of multidrug resistance in bacterial uropathogens from Kathmandu, Nepal

Abstract: BackgroundUrinary Tract Infection (UTI) is one of the most common infectious diseases and people of all age-groups and geographical locations are affected. The impact of disease is even worst in low-resource developing countries due to unaware of the UTIs caused by multidrug-resistant (MDR) pathogens and the possibility of transfer of MDR traits between them. The present study aimed to determine the prevalence of MDR bacterial isolates from UTI patients, the antibiotic resistance pattern and the conjugational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

44
81
12
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 154 publications
(138 citation statements)
references
References 31 publications
44
81
12
1
Order By: Relevance
“…Of the 33 MDR isolates, 27(45.0%) were E. coli. This result was supported by previous other studies 21,22,23 . Our study demonstrated the highest resistance to Ceftriaxone (94.12%) among 17 MDR isolates.…”
Section: Discussionsupporting
confidence: 83%
“…Of the 33 MDR isolates, 27(45.0%) were E. coli. This result was supported by previous other studies 21,22,23 . Our study demonstrated the highest resistance to Ceftriaxone (94.12%) among 17 MDR isolates.…”
Section: Discussionsupporting
confidence: 83%
“…The prevalence of UTIs was 41.7% in the present study, supporting previously reported results (3,4). Most frequently, E. coli, P. aeruginosa, or K. pneumoniae are isolated in urine cultures after a UTI develops (11,(16)(17)(18). E. coli was the most frequently detected uropathogen in our study, followed by P. aeruginosa and K. pneumoniae, findings that concurs with previous studies (11,(16)(17)(18).…”
Section: Discussionsupporting
confidence: 83%
“…Our findings were consistent with the findings by Shrestha et al [5] who reported the culture positivity of 29.8% in females and 15.2% in males. In a similar study by Baral et al [6] the growth positivity was 33.5% among female patients and 23.7%, in male patients. This higher growth positivity seen in females was found to be statistically significant (p<0.05) and is due to their anatomical structure (short urethra and proximity to anal orifice) leading to easy access for enteric bacteria.…”
Section: Discussionmentioning
confidence: 71%